Targeted Delivery of 5-Fluorouracil and Sonidegib via Surface-Modified ZIF-8 MOFs for Effective Basal Cell Carcinoma Therapy - Bharath Singh Padya; Gasper Fernandes; Sumukha Hegde; Sanjay Kulkarni; Abhijeet Pandey; Praful Balavant Deshpande; Sheikh F. Ahmad; Dinesh Upadhya; Srinivas Mutalik (MDPI AG, 2023)
The therapeutic effectiveness of the most widely used anticancer drug 5-fluorouracil (5-FU) is constrained by its high metabolism, short half-life, and rapid drug resistance after chemotherapy. Although various nanodrug delivery systems have been reported for skin cancer therapy, their retention, penetration and targeting are still a matter of concern. Hence, in the current study, a topical gel formulation that contains a metal-organic framework (zeolitic imidazole framework; ZIF-8) loaded with 5-FU and a surface modified with sonidegib (SDG; acting as a therapeutic agent as well as a targeting ligand) (5-FU@ZIF-8 MOFs) is developed against DMBA-UV-induced BCC skin cancer in rats. The MOFs were prepared using one-pot synthesis followed by post drug loading and SDG conjugation. The optimized MOFs were incorporated into hyaluronic acid-hydroxypropyl methyl cellulose gel and further subjected to characterization. Enhanced skin deposition of the 5-FU@ZIF-8-SDG MOFs was observed using ex vivo skin permeation studies. Confocal laser microscopy studies showed that 5-FU@ZIF-8-SDG MOFs permeated the skin via the transfollicular pathway. The 5-FU@ZIF-8-SDG MOFs showed stronger cell growth inhibition in A431 cells and good biocompatibility with HaCaT cells. Histopathological studies showed that the efficacy of the optimized MOF gels improved as the epithelial cells manifested modest hyperplasia, nuclear pleomorphism, and dyskeratosis. Additionally, immunohistochemistry and protein expression studies demonstrated the improved effectiveness of the 5-FU@ZIF-8-SDG MOFs, which displayed a considerable reduction in the expression of Bcl-2 protein. Overall, the developed MOF gels showed good potential for the targeted delivery of multifunctional MOFs in topical formulations for treating BCC cancer.